(untitled) (Nordic Journal of African Studies, 2011)
Kambaata (Highland East Cushitic) is an aspect-marking language with a prominent opposition between perfective and imperfective aspect. The absolute location of an event in time (tense) is expressed by devices other than verbal inflection or inferred from the aspectual value of a verb. The present article discusses the devices that are applied to encode future in Kambaata. Firstly, imperfective verb forms can be interpreted as expressing future reference. Secondly, the language has grammaticalised two purpose constructions into imminent and/or intentional future constructions. Furthermore, certain converb forms can be used to express that events in subordinate clauses are later in time than events expressed in the matrix clause. A comparison with related languages shows that Kambaata is a typical Highland East Cushitic language, as far as the means used to encode future time reference are concerned.